Cranial Metastasis as Initial Manifestation of Hepatocellular Carcinoma - Vina Tri Aditya; Harijono Achmad (The Indonesian Society for Digestive Endoscopy, 2014)
Cranial metastasis from hepatocellular carcinoma (HCC) prior to diagnosis of the primary tumor withoutliver dysfunction is a very rare event. Cranial metastasis may be the sole initial presentation of HCC. Earlydiagnosis is essential in order to treat the primary disease. Cranial metastasis from HCC should be consideredin the differential diagnosis in patients with subcutaneous scalp mass and osteolytic defects on X-ray.A 55 year old female patient without known liver disease, presented with a palpable right occipital scalp mass. On head computed tomography (CT) scan, a tumor on right orbita wall, osteolytic skull and invasion to theright frontal lobe was observed. The histological diagnosis obtained from the biopsy was a poorly differentiatedcranial metastasis adenocarcinoma that was difficult to determine the origin. On positron emission tomography(PET) scan, there was a hypermetabolic mass around intra hepatal bile duct which suspicious primary cancer.The histological diagnosis obtained from the liver biopsy was appropriate with HCC grade II. The metastatictumor was removed via occipital craniectomy. She received a palliative course of external beam radiationtherapy to the right orbit. Then, she received symptomatic treatment and herbal medicine with cassava leavesfor the last three months. Evaluation of bone survey shows lytic lesion at calvaria and compression fractureat vertebrae thoracal 11-12 appropriate with metastasis process. According to Barcelona Clinic Liver Cancer(BCLC) criteria she suffered from HCC terminal stage D with average survival of about 4 months.Keywords: hepatocellular carcinoma, cranial metastasis, palliative treatment ABSTRAKMetastasis kranial dari karsinoma hepatoselular sebelum diagnosis tumor primer dengan hasil tanpa adanyagangguan fungsi hati adalah peristiwa sangat jarang ditemui. Metastasis pada tulang kranial dapat menjadi salah satu presentasi awal dari karsinoma hepatoseluler. Menegakkan diagnosis di awal sangat diperlukan untuk menentukan penatalaksanaan pada penyakit primer. Metastasis pada kranial dari karsinoma hepatoseluler harusdipertimbangkan pada kasus subkutan skalp tumor dan pada pasien dengan defek osteolitik pada gambaranradiologi.Seorang pasien perempuan usia 55 tahun, yang tidak didapatkan riwayat penyakit hati sebelumnya, datangdengan benjolan pada region oksipital kanan. Hasil computed tomography (CT) scan kepala didapatkantumor pada dinding orbita kanan. Dari pemeriksaan histologi menunjukkan metastasis dari adenokarsinomaberdiferensiasi buruk yang sulit ditentukan asalnya. Pada pemeriksaan positron emission tomography (PET)scan, terdapat massa hipermetabolik di sekitar duktus intrahepatik yang diduga sebagai tumor primer. Hasil biopsi menunjukkan karsinoma hepatoselular derajat 2. Dilakukan kraniektomi region oksipital pada penyebaran tumor dan dilanjutkan radioterapi paliatif pada region oksipital kanan. Selanjutnya pasien hanya mendapatkanterapi simtomatik dan daun singkong sebagai terapi herbal selama 3 bulan terakhir. Evaluasi survei tulangsetelah 3 bulan menunjukkan lesi litik pada kalvaria dan fraktur kompresi pada tulang vertebrae thorakal 11- 12. Menurut kriteria Barcelona Clinic Liver Cancer (BCLC) pasien tersebut masuk ke dalam stadium terminalD dengan rata-rata angka harapan hidup 4 bulan setelah terdiagnosis.Kata kunci: karsinoma hepatoseluler, metastasis kranial, terapi paliatif